Burnout among medical residents in Haiti: a mixed-methods study - Ornella Sainterant; Emmanuel Mathieu; Ludentz Dorcélus; Vernet Etienne; Kesnel Dorestant (BMJ Open)
Objectives To investigate the prevalence and risk factors associated with burnout among residents and to explain their experiences with burnout.Design Mixed-methods convergent parallel study with an explanatory follow-up.Settings One tertiary hospital in Mirebalais and one community hospital in Saint-Marc.Participants Of the 127 registered residents in both settings, 26 were excluded because they were on leave. Therefore, 101 were asked to participate. We received responses from 98 residents (response rate 97.02%).Interventions Data collection took part in two stages: quantitative data collection was first made over a 2-week period in July 2023 using a questionnaire which included the Maslach Burnout Inventory. We simultaneously conducted a qualitative analysis based on three questions around which stress factors were related to work, personal fulfilment and social issues in the questionnaire. Second, following preliminary data results, one focus group was held with the seven chief residents to bring an in-depth understanding of the quantitative data analysis from the study questionnaire.Primary and secondary outcomes Sociodemographic and clinical factors linked to burnout for quantitative data. The themes explored for qualitative data were stress factors related to work, personal fulfilment and social issues. One focus group held with the chief residents explained, based on preliminary results, the main causes of burnout among medical residents, influencing factors, coping strategies and perspectives.Results Five major findings emerged from the quantitative data, including the following: (a) burnout prevalence was 79.59%; (b) 43% of the residents estimated working more than 80 hours/week; (c) the group with the highest burnout rates were the second-year postgraduate residents (p=0.01); (d) paediatrics and family medicine residents had the highest mean score of emotional exhaustion (p=0.01); (e) general surgery/orthopaedics and paediatrics had the highest mean score of depersonalisation (p<0.01). For the qualitative data, five categories were linked to burnout: the residents’ quality of life, their feelings of ineffectiveness, their regrets for choosing to do residency in Haiti, the hospital’s admission policy and social factors.Conclusions Burnout prevalence was significantly high. The medical education department needs to implement initiatives that improve patient healthcare, boost the residents’ morale and comply with accreditation standards. A cohort study or quality improvement project investigating the impact of interventions might also be suitable, or a study at different times of the academic year and in a less volatile period of time in Haiti might provide a more complete picture of the onset of this syndrome.